(untitled) (Research Papers, 2022)
The article compares the strategies of Washington, London and Paris for the Indo-Pacific region (object of analysis), which after the US withdrawal from Afghanistan emerges as a strategic zone of confrontation, the dynamics of which will largely determine global stability/ instability. The trilateral agreement AUKUS as an alternative to the Quad, in which Britain is a non-regional player with serious ambitions in the Indo-Pacific, is problematize. >problematic. The aim is to track trends that will reflect on the future of the EU.